Penetapan Biaya Berdasarkan Aktivitas - Faujiah Faujiah; Haliza Haliza; Novida Niasari Harahap (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The system is a framework of interconnected procedures that are arranged in accordance with an overall scheme to carry out an activity or main function of the company and is aimed at achieving the set goals, while the procedure is a sequence of jobs involving several people in a part. or more in carrying out an activity. With the existence of a system, the company's activities will be more directed and organized, so that the targets set are more easily achieved. One type of system that has a very important role in the company is the accounting system. The application of an appropriate accounting system with all the conditions and situations faced by the company greatly assists the smooth running of transactions carried out by the company while at the same time providing data or information needed by management in making decisions and exercising supervision in order to operate the company efficiently. A good accounting system will better guarantee that transactions that occur within the company will run more smoothly and will be better protected from all forms of fraud. Without an adequate accounting system, it will be more difficult to control transactions, and it is easy to abuse them for the personal interests of the parties involved. Activity based costing (activity based costing ABC) is a method of charging activities based on the amount of resource usage, and assigning costs to cost objects, such as products or customers, based on the size of the activity, as well as to measure the cost and performance of activities related to the process and cost objects. In Activity Based Costing (ABC) all costs are charged to products that generate activity or if there is a fundamental reason that these costs are affected by the product being made, both production costs. as well as non-production costs This method is a more accurate cost discovery. ABC is also a relatively recent innovation in cost accounting. ABC can be used quickly by companies operating in the industrial sector and in government and non-profit organizations.